Sistem Rekomendasi Produk Skincare Halal Berbasis Komposisi Bahan menggunakan Metode Simple Additive Weighting - Velisa Amanda Putri; Sri Winiarti; Nurkhasanah Nurkhasanah (Universitas Negeri Gorontalo, 2026)
The rapid development of the skincare industry has increased the complexity of product ingredient composition, making it difficult for consumers to determine products that suit their skin needs. This challenge is even more complex for Muslim consumers who must consider the halal aspects of skincare product ingredients. Lack of understanding regarding ingredient content, skin problems, skin type, and product halal status leads to a high risk of errors in skincare selection. Therefore, this study aims to implement a halal skincare product recommendation system based on ingredient content using the Simple Additive Weighting (SAW) method. The system uses seven criteria: ingredient content, halal logo, BPOM logo, ingredient safety, skin problems, skin type, and age. Alternatives consist of 61 skincare products, 22 facial washes, 23 moisturizers, and 16 sunscreens obtained from questionnaires with 300 respondents. The novelty of this study lies in the integration of halal aspects, skin conditions, and government regulations in a multi-criteria decision-making (MCDM)-based decision-making model. The SAW method is used to weight and rank alternatives based on preference values. The results show that the SAW method is able to generate product recommendations according to user characteristics. For normal-dull skin conditions, the best recommendations are Emina Bright Prebiotic Tranexamic (0.7800), Somethinc Skin Goals Moisture Silk Creme (0.8300), and Wardah UV Shield Active Protection Serum SPF 50 PA++++ (0.7050). For sensitive-acne skin conditions, the best recommendations are Skintific 3x Acid Acne Gel Cleanser (0.9750), Something Acne Treatment Moisturizer Gel (1.0000), and Wardah UV Shield Acne Calming Sunscreen SPF 50 PA++++ (0.8300). The results of the Black Box Testing showed that all system functions were running well, while the expert judgment by a dermatology specialist showed that the system was running well.